Characterization of the influence of chlororespiration on the regulation of photosynthesis in the glaucophyte Cyanophora paradoxa - Misumi, Masahiro (Sci Rep, 2017)
Glaucophytes are primary symbiotic algae with unique plastids called cyanelles, whose structure is most similar to ancestral cyanobacteria among plastids in photosynthetic organisms. Here we compare the regulation of photosynthesis in glaucophyte with that in cyanobacteria in the aim of elucidating the changes caused by the symbiosis in the interaction between photosynthetic electron transfer and other metabolic pathways. Chlorophyll fluorescence measurements of the glaucophyte Cyanophora paradoxa NIES-547 indicated that plastoquinone (PQ) pool in photosynthetic electron transfer was reduced in the dark by chlororespiration. The levels of nonphotochemical quenching of chlorophyll fluorescence was high in the dark but decreased under low light, and increased again under high light. This type of concave light dependence was quite similar to that observed in cyanobacteria. Moreover, the addition of ionophore hardly affected nonphotochemical quenching, suggesting state transition as a main component of the regulatory system in C. paradoxa. These results suggest that cyanelles of C. paradoxa retain many of the characteristics observed in their ancestral cyanobacteria. From the viewpoint of metabolic interactions, C. paradoxa is the primary symbiotic algae most similar to cyanobacteria than other lineages of photosynthetic organisms.